2010
DOI: 10.1007/s12550-010-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of aflatoxin B1 production by Aspergillus parasiticus in bee pollen of Greek origin

Abstract: Aflatoxin B1 (AFB1) is a carcinogenic metabolite produced by certain Aspergillus species such as A. parasiticus and A. flavus. The beneficial properties of bee pollen have transformed this commodity into an increasingly frequent component of the human diet. As bee pollen is a substrate on which aflatoxigenic fungi can grow, AFB1 production is likely. In the present study, we describe a method for aflatoxin B1 determination in bee pollen utilising high pressure liquid chromatography (HPLC) with a fluorescence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recently, aflatoxin B1 production by Aspergillus parasiticus in commercial bee pollen of Greek origin was studied [29]. It is noteworthy that mycotoxins, which are compounds of known toxicity, are not involved in the primary search for pollen or honey product contamination but the results showed in this work would indicate that strains with the ability for a variety of mycotoxin production may be widely present in these products, which are increasingly consumed.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, aflatoxin B1 production by Aspergillus parasiticus in commercial bee pollen of Greek origin was studied [29]. It is noteworthy that mycotoxins, which are compounds of known toxicity, are not involved in the primary search for pollen or honey product contamination but the results showed in this work would indicate that strains with the ability for a variety of mycotoxin production may be widely present in these products, which are increasingly consumed.…”
Section: Discussionmentioning
confidence: 84%
“…High level of total aflatoxins were found in Slovakian poppy bee pollen (up to 16.20 μg kg -1 ) and rape bee pollen (up to 5.40 μg kg -1 ), while this concentration was lower in the samples of sunflower bee pollen (Kačaniová et al, 2011). In Greece in the study of Pitta and Markaki (2010) AFB 1 was not found in a batch sample of bee pollen with natural mycobiota throughout the 20 days of incubation period, but when bee pollen was used as a substrate for inoculation of A. parasiticus, AFB 1 was detected in inoculated samples after the 3 rd day of incubation. According to the results of González et al (2005) toxigenic potential of toxigenic Aspergillus isolates was in range from 3.5 to 9.3 μg AFB 1 kg -1 .…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, it was observed that the species from the genera Aspergillus and Penicillium isolated from Slovakian pollen should be consider as the most important producers of mycotoxins (Kačaniová and Fikselová, 2007). AFB 1 was not detectable in the batch samples of Greek bee pollen with natural mycobiota, but if the bee pollen substrate was inoculated with A. parasiticus, AFB 1 was detected (Pitta and Markaki, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…More than a hundred mycotoxins are known, and most of them are produced by some of the species belonging to one of three fungi genera: Aspergillus , Penicillium and/or Fusarium [34]. According to the available literature [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50] the presence of the following mycotoxins in pollen has been investigated or proved with appropriate analytical methods and analysis: Aflatoxins (AFs), ochratoxins (OTs), fumonisins (FBs), zearalenone (ZEN), deoxynivalenol (DON), and its acetoxy derivative, T-2 toxin (T-2), HT-2 toxin, fusarenon-X, diacetoxyscirpenol, nivalenol, neosolaniol, roridin A, verrucarrin A, α-β-dehydrocurvularin, phomalactone,6-(1-propenyl)-3,4,5,6-tetrahydro-5-hydroxy-4H-pyran-2-one, 5-[1-(1hydroxibut-2-enyl)]-dihydrofuran-2-one and 5-[1-(1-hydroxibut-2-enyl)]-furan-2-one.…”
Section: Mycotoxins In Pollenmentioning
confidence: 99%